Electrochemical, Characterization, and Quantum Chemical Studies of Two Newly Synthesized Aromatic Aldehydes-Based Xanthene Diones as Corrosion Inhibitors for Mild Steel in 1 M Hydrochloric Acid - Galai, M.; Touhami, M. Ebn; Oubaaqa, M.; Dahmani, K.; Ouakki, M.; Khattabi, M.; Boukhris, S. (Springer Science and Business Media Deutschland GmbH, 2023)
The inhibiting effect of two newly synthesized inhibitors, namely 3,3,6,6-tetramethyl-9-phenyl-3,4,6,7-tetrahydro-2H-xanthenes-1,8(5H,9H)-dione (ZM-1) and 9-(4-Bromophenyl)-3,3,6,6-tetramethyl-3,4,5,6,7,9-hexahydro-2H-xanthene-1,8-dine (ZM-2) on mild steel (MS) corrosion in 1 M HCl solution has been examined. For this purpose, Electrochemical Impedance Spectroscopy (EIS) and Potentiodynamic Polarization measurements (PP) have been carried out. Furthermore, theoretical chemistry concepts have been used to calculate and analyze the molecule’s quantum parameters. This has been accomplished using Density Functional Theory (DFT). Molecular Dynamic Simulation has been used to interpret the inhibiting action mode. It has been perceived that the increase of inhibitor concentration managed to significant corrosion rate reduction of MS in 1 M HCl, with inhibitive efficiency values reaching, respectively, 84% and 87% at 10?3 M inhibitor concentrations of ZM-1 and ZM-2. The inhibition efficiency is augmented with an inhibitor concentration increase. Temperature influence on the corrosion behavior of MS in 1 M HCl at the inhibitor’s optimal concentration of 10?3 M was studied in the range of temperature 298–328 K. Polarization plots showed that ZM-1 and ZM-2 acted as mixed-type inhibitors. The adsorption mechanism of the studied inhibitors was consistent with the Langmuir isotherm model. The corroded surface has also been analyzed by SEM/EDX; AFM, contact angle, and XRD techniques. © 2023, The Author(s), under exclusive licence to Springer Nature Switzerland AG.
Keywords: Acid corrosion; AFM; Computational calculations; DFT; Electrochemical investigations; Mild steel; SEM–EDX; Xanthene diones